The Link Between Innovation Behaviors and Productivity Strategies of Enterprises in Albanian Economic Growth - Turan, Güngör; Gjana, Ima (European Journal of Economics and Business Studies, 2015)
The paper primarily aims to provide a link between the innovation behaviors and productivity levels of enterprises in Albania, which are the main source of job creation and employment in economic growth, as well as underscore the importance that the innovation behaviors and productivity strategies of enterprises play in Albanian growth in the long-run. The regression model developed and Johansen co-integration test applied on the data of GDP per worker and the number of created jobs or employed in 1991-2013, are investigated with the scanted literature throughout the study.